Production improvement by using immiscible simulataneous water alternating gas (SWAG) injection in Tapis field [electronic resource] - Nur Hidayah Bohari, 1988- (2011)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2011